Sistem Otomatisasi Pompa Air Berbasis Arduino Uno Dengan Kontrol Waktu Menggunakan Sensor RTC DS3231 - Surur, Muhammad Misbakhus; Fahrizal, Mochammad Safri; Pradana, Dava Andhika Putra; Rohmad, Chabibur; Shidiq, Ahmad (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
An automatic water pump control system based on Arduino Uno and RTC DS3231 sensor was developed to optimize water usage in irrigation and household applications. The system integrates a high-precision RTC module (±2 ppm) to maintain time accuracy and an Arduino microcontroller as the main controller. The water pump is activated automatically based on a programmed schedule, with a time tolerance of ±2 minutes during a 30-day test. Experimental results show energy savings of up to 40% compared to manual operation, as well as an increase in watering accuracy of 98.7%. The system is equipped with a flexible schedule programming interface via a computer, allowing adaptation to various irrigation scenarios. Other advantages include low production costs (Rp 250,000) and ease of installation.